Answer:
1.) x={1,−2}
2.) x={3,-9}
3.) x = {4, 4}
4.) x={0, 12}
5.) x = {6, 8}
Explanation:
1.) x2+x-2=0
Step-1 : Multiply the coefficient of the first term by the constant 1 • -2 = -2
Step-2 : Find two factors of -2 whose sum equals the coefficient of the middle term, which is 1 .
-2 + 1= -1
-1+ 2= 1 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -1 and 2
x2 - 1x + 2x - 2
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-1)
add up the last 2 terms, pulling out common factors :
2 • (x-1)
Step-5 : Add up the four terms of step 4 :
(x+2) • (x-1)
(x + 2) • (x - 1) = 0
Hope this Helps!!!!